2022
DOI: 10.1155/2022/9488047
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy Evaluation of High-Volume Hemofiltration in Patients with Severe Acute Respiratory Distress Syndrome

Abstract: Objective. To investigate the efficacy of high-volume hemofiltration (HVHF) in the treatment of severe acute respiratory distress syndrome (ARDS) caused by sepsis and its effect on serum levels of miR-126, miR-184, and MAP1-LC3. Methods. From July 1, 2015 to December 31, 2021, patients with severe ARDS caused by sepsis who were admitted to our hospital were retrospectively analyzed. Patients who received conventional treatment were summarized into the control group, and those who received HVHF were summarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%